Instruments for Measuring Patient Safety Competencies in Clinical Settings: A Literature Review - Suciati, Suciati; Asmaningrum, Nurfika; Suhari, Suhari (Indonesian Journal of Global Health Research, 2024)
Patient safety culture has emerged as a global priority necessitating improvement to prevent patient accidents. Measuring the competency of healthcare workers concerning patient safety within health services is essential, and various instruments can be employed for this purpose. This study aims to analyze the instruments used to measure patient safety competency. Method: A systematic review was conducted using the PRISMA protocol and the JBI assessment tool to identify eligible articles. Two electronic databases, PubMed and Google Scholar, were searched. The keywords used in the research included “instrument safety culture in clinical settings”; “Safety culture instrument”; "instrument for patient safety culture". Inclusion criteria encompassed research on instruments measuring patient safety competency, published in English within the last ten years (2014-2024). Results: The review identified 15 articles that met the inclusion criteria. Four types of instruments were commonly used to measure patient safety competency: the Safety Attitudes Questionnaire (SAQ), the Manchester Patient Safety Framework (MaPSAF), the Hospital Survey on Patient Safety Culture (HSOPSC), and the TeamSTEPPS Teamwork Perceptions Questionnaire (T-TPQ). Conclusion: The instruments SAQ, MaPSAF, HSOPSC, and T-TPQ have demonstrated effectiveness in measuring various dimensions related to patient safety culture. To optimize the assessment of patient safety culture within health service facilities.